2023
DOI: 10.1007/s11069-023-05949-4
|View full text |Cite
|
Sign up to set email alerts
|

FDI and CO2 emissions in developing countries: the role of human capital

Abstract: FDI inflows remain an important source of economic growth and technology transfer for developing countries. However, the proponents of the pollution haven hypothesis (PHH) argue that FDI inflows may result in the production of polluted goods in poor economies. The empirical testing of PHH reveals conflicting outcomes on the subject. This study argues that foreign firms’ choice of specific technologies and hence the validity of PHH can be determined by host countries’ level of education. For developing economie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(6 citation statements)
references
References 80 publications
1
5
0
Order By: Relevance
“…The second study findings suggested either a negative impact from: tourism and economic growth, whereas a positive effect was observed from energy consumption, and population, aligning with the results of Wahyudi et al [18]. Khan et al [19], in developing countries, and Voumik and Ridwan [20] reached a positive association between CO 2 emissions and each of the variable: population growth and FDI, in Argentina from 1972 to 2021. Javed et al [8] demonstrated that economic growth, FDI, energy consumption and exports have a positive impact.…”
Section: The Impact Of Socio-economic Factors and Energy Consumption ...supporting
confidence: 83%
See 1 more Smart Citation
“…The second study findings suggested either a negative impact from: tourism and economic growth, whereas a positive effect was observed from energy consumption, and population, aligning with the results of Wahyudi et al [18]. Khan et al [19], in developing countries, and Voumik and Ridwan [20] reached a positive association between CO 2 emissions and each of the variable: population growth and FDI, in Argentina from 1972 to 2021. Javed et al [8] demonstrated that economic growth, FDI, energy consumption and exports have a positive impact.…”
Section: The Impact Of Socio-economic Factors and Energy Consumption ...supporting
confidence: 83%
“…Our result is similar to Apergis [24], and partially similar to Belloumi et Alshehry [15], regarding the non significance in the short term, and opposite for the long term which had a positive impact. However, conflicting results exist, with some authors, such as Farhan et al [76] and Khan et al [19], suggesting a positive impact, while others, including Tahir [26] and Basuki and Stioningrum [22], demonstrating a negative effect.…”
Section: Discussionmentioning
confidence: 99%
“…Surprisingly, we found that environmental innovations do not have a noticeable impact on environmental sustainability in the studied countries. Khan et al (2023) demonstrated the relationship between foreign direct investment in developing countries (FDI), technology transfer and human capital and the carbon intensity of the economy. Data collected from 2000 to 2016 from 108 developing countries show that FDI helps to decrease CO2 emissions in countries that enhance their human capital quality due to education.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Similar studies, taking into account additional factors (e.g. energy consumption, renewable energy consumption, national income per capita, investment, exports, imports) have also been performed by other authors, and a synthetic summary of existing studies of short-and long-term relationships is included in Khan et al (2023).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The development of fundamental infrastructure, such as trains and roads, to enhance connectivity among the nations involved in the BRI has considerably facilitated trade between them. However, this progress has come at the expense of heightened CO 2 emissions [ 16 ]. Therefore, when comparing BRI nations to non-BRI countries, it is more probable that ICT progress in BRI countries will favor extending industrial size and increasing CO 2 emissions.…”
Section: Introductionmentioning
confidence: 99%